Dementia Is Induced via the AGEs/Iba1/iNOS Pathway in Aged KK-Ay/Tajcl Mice - Keiichi Hiramoto; Masashi Imai; Shota Tanaka; Kazuya Ooi (Life, 2023)
The onset and exacerbation of dementia have been observed in elderly patients with type 2 diabetes. However, the underlying mechanism remains unclear. In this study, we investigated the effects of aging on the cognitive function in a mouse model of type 2 diabetes. Pathogen-free KK-Ay/TaJcl mice were used in this study. The cognitive abilities and memory declined in the mice and worsened in the 50-week-olds. The levels of advanced glycation end products (AGEs), receptor for AGE (RAGE), and Iba1 in the hippocampus were increased in the mice compared to those in the control mice. Hippocampal levels of CC-chemokine receptor 7 and inducible nitric oxide synthase, which are from M1-type macrophages that shift from microglia, were higher in KK-Ay/TaJcl mice than in control mice. Tumor necrosis factor (TNF)-α and nitric oxide (NO) levels secreted by M1-type macrophages were similarly elevated in the mice and were even higher at the age of 50 weeks. NO levels were markedly elevated in the 50-week-old mice. In contrast, differentiation of CD163 and arginase-1 did not change in both mouse types. Memory and learning declined with age in diabetic mice, and the AGEs/RAGE/M1-type macrophage/NO and TNF-α pathways played an important role in exacerbating memory and learning in those mice.